MENGGAUNGKAN WISATA PEDESAAN MELALUI KULINER YELLOW CHIPS PUMPKIN (YECHIPUM) KHAS DESA PADUSAN, MOJOKERTO - Ridhoi, Ronal; Oktaviani, Rosyida; Nuriansyah, Jati Saputra; Putri, Dhika Maha (Universitas Negeri Malang, 2023)
ECHOING RURAL TOURISM THROUGH CULINARY YELLOW CHIPSPUMPKIN (YECHIPUM) TYPICAL OF PADUSAN VILLAGE, MOJOKERTO Pumpkin can be used as a basic ingredient for making typical village culinary in the form ofcookies. However, pumpkin has not been used optimally by rural communities as a traditionalregional culinary product, in this case, Padusan Village, Mojokerto Regency. This paper aims to:(1) provide education on the potential utilization of pumpkin as the main raw material for Padusanspecial culinary; (2) developing an innovative micro business at Padusan Village; (3) provideinformation on how unique and attractive branding is. By using the training method, this papertries to help and assist the residents of Padusan Village to take advantage of the opportunity tocreate a culinary industry made from pumpkin. In this study, pumpkin is processed into drycookies called Yechipum, an acronym for Yellow Chips Pumpkin. After conducting training andpractice with culinary practitioners, it can be concluded that Yechipum can be a typical souvenirof Padusan Village as a culinary support for rural tourism. In addition, the branding that has beenmade also has a novelty that can produce HKI for Padusan Village and also State University ofMalang. Labu kuning dapat digunakan sebagai bahan dasar pembuatan kuliner khas desa dalam bentukcookies. Meski demikian, labu kuning belum dimanfaatkan secara maksimal oleh masyarakatpedesaan sebagai produk kuliner tradisional khas daerah, dalam hal ini yaitu Desa PadusanKabupaten Mojokerto. Tulisan ini bertujuan untuk: (1) memberikan edukasi pemanfaatan potensilabu kuning sebagai bahan baku utama kuliner khas Padusan; (2) mengembangkan bibit-bibitUMKM baru di Desa Padusan yang inovatif; (3) memberikan informasi bagaimana branding yangunik dan menarik. Dengan menggunakan metode pelatihan, tulisan ini berusaha membantu danmendampingi warga Desa Padusan memanfaatkan peluang untuk membuat industri kulinerberbahan dasar labu kuning. Dalam kajian ini, labu kuning diproses menjadi cookies kering yangdiberi nama Yechipum, akronim dari Yellow Chips Pumpkin. Setelah melakukan pelatihan danpraktik bersama praktisi kuliner, dapat disimpulkan bahwa Yechipum bisa menjadi oleh-oleh khasDesa Padusan sebagai kuliner penunjang wisata pedesaan. Selain itu, branding yang telah dibuatjuga mempunyai novelty yang dapat menghasilkan HKI untuk Desa Padusan dan UniversitasNegeri Malang.